Weltkarten der Relation von fühlbarer und latenter Wärme - Lauer, Wilhelm; Frankenberg, Peter (ERDKUNDE, 1982)
Based upon the equivalent temperature a formula is given to calculate the ratio of sensible and latent heat. The regional pattern of the July and January ratio is presented in two maps. The maps clearly show the spatial effect of the two main climatic types: aridity and humidity in the tropics, continentality and oceanity in the outer tropics. The ratio can be considered as a very appropriate indicator of bioclimatological phenomena.